Differential expression of ABO in normal and tumor tissues: Implications for cancer biology and prognosis - Hind M. Albadrani, PhD; Munerah Hamed, PhD; Abeer Zakariyah, PhD; Samar Binkheder, PhD; Saeed M. Kabrah, PhD; Arwa F. Flemban, PhD (Journal of Taibah University Medical Sciences)
الملخص: أهداف البحث: تعرف فصيلة ABO في المقام الأول بتحديد فصائل الدم، وأظهرت الدراسات أنماط تعبير متغيرة في الأنسجة المختلفة وأنواع السرطان. وتهدف هذه الدراسة البحث في العلاقة بين التعبير الجيني للفصيلة والسرطان، وتقييم تأثيره المحتمل على بقاء المريض على قيد الحياة. طرق البحث: باستخدام قاعدة بيانات GEPIA، قمنا بتحليل تعبير ABO في الأنسجة الطبيعية والأورام عبر أنواع السرطان المختلفة باستخدام أدوات التحاليل الجينية المتاحة عبر الإنترنت لإجراء تقييم شامل. النتائج: كشف التحليل عن تباينات كبيرة في التعبير عن ABO بين أنواع الأنسجة المختلفة. والجدير بالذكر أن أنسجة المبيض والغدة الدرقية أظهرت أعلى تعبير عن ABO، في حين أظهرت أنسجة الكبد والغدة الصعترية والدماغ تعبيرًا منخفضًا نسبيًا. وتباينت أنماط التعبير عن ABO بشكل واضح بين أنواع السرطان، حيث أظهرت سرطانات المبيض والغدة الدرقية الاختلافات الأكثر أهمية بين أنسجة الورم والأنسجة الطبيعية. كما أظهرت أنواع أخرى من السرطان، بما في ذلك سرطان قشرة الكظر، وسرطان الدم النقوي الحاد، وسرطان الخلايا الكلوية، اختلافات ملحوظة في التعبير عن ABO. وارتبط انخفاض التعبير عن ABO بانخفاض معدلات البقاء على قيد الحياة في سرطان الغدة الدرقية القولون والمستقيم، وسرطان الغدة الدرقية في المعدة، وسرطانات الكلى، وغيرها. الاستنتاجات: تشير هذه النتائج إلى الدور المحتمل لـ ABO في تطور الورم وتطور السرطان والتشخيص. كما تؤكد هذه الدراسة على قيمة ABO كمؤشر حيوي لمختلف أنواع السرطان وتتطلب إجراء المزيد من البحث لفهم أدواره الوظيفية وتأثيراته العلاجية لتطوير علاجات السرطان المستهدفة وأدوات التشخيص. Abstract: Objectives: ABO, which is primarily recognized for determining blood types, shows variable expression patterns in different tissues and cancer types. This study investigated the relationship between gene expression and cancer, and assessed its potential impact on patient survival. Methods: Utilizing the GEPIA database, we analyzed ABO expression in normal and tumor tissues across various cancer types using online in silico tools for comprehensive evaluation. Results: The analysis revealed significant disparities in ABO expression among different tissue types. Notably, ovarian and thyroid tissues exhibited the highest expression of ABO, whereas the liver, thymus, and brain tissues showed relatively low expression. The expression patterns of ABO varied distinctly among cancer types, with ovarian and thyroid carcinomas demonstrating the most significant differences between tumor and normal tissues. Other cancers, including adrenocortical carcinoma, acute myeloid leukemia, and renal cell carcinoma, also exhibit notable variations in ABO expression. Low ABO expression was correlated with reduced survival rates in colorectal adenocarcinoma, stomach adenocarcinoma, and renal cancers, among others. Conclusions: These findings suggest the potential role of ABO in tumor development, as well as cancer progression and prognosis, underscoring the value of ABO as a biomarker for various cancers. This warrants further research for understanding the functional roles of ABO and its therapeutic implications to develop targeted cancer therapies and diagnostic tools.